Blogging Family-like Relations when Visiting Theme and Amusement Parks: The Use of Children in Displays Online - Anne-Li Lindgren; Anna Sparrman (Culture Unbound: Journal of Current Cultural Research, 2014)
This paper combines sociological perspectives on family display, internet studies on family and private photography and a child studies perspective on the display of children. The paper proposes that blogging practices related to visits to theme and amusement parks in Sweden provide a new arena for people to display family-like relationships. In the different displays, adults mainly use pictures of children in the blogs to demonstrate their ability to perform family-like relationships. The paper suggests that this form of child-centred display, a visualized child-centredness, done during the park visit as well as in the blogging, is part of the construction of contemporary childhoods and what it means to be a child today and has not been theorized in earlier research on the display of family-like relations.